ASSESSMENT OF ENERGY TRANSITION BASED ON RENEWABLE ENERGY POTENTIAL IN UGANDA - KYAGABA DENIS (Graduate School of International Studies Ajou University, 2024)
Background: Waning global warming to 1.5 degrees celicious and enabling socio-economic development aspect that is inclusive and equitable are the world’s pressing challenges. To achieve the targets of the Paris Agreement on climate change, Africa must forego burning 90% of known reserves of coal, 34% of gas and 26% of oil (UNU-INRA, 2019). In Uganda, hydropower largely facilitates renewable energy access for social and productive use, most of energy service sub-sectors are still utilizing biomass and fossils as their main primary energy source However, this status quo needs to be waned by a shift to development and utilization of new and renewables (energy transition). Due to insufficient empirical evidence, it’s not clear whether Uganda as developing country, will achieve this energy transition by 2050. This study was therefore meant to analyze the possibilities of energy transition in Uganda based on existing renewable energy resource potential. Methods: The three scenarios were developed, i . e . solar-promo, Fixed-hydro, and the m e r g e d case, t h e s e w e r e r a n using the GCAM-EML, the calibrated data (as a reference case) was benchmarked and validated from Ugandan country’s data (MEMD, 2020) as well as IEA data, World Bank, and IRENA. Keyed in the scenario files, run through prepared model workspace. The reference scenario represents a case where no policy implication related to energy transition pathways in adopting RE resources potential (RE’s) over the modeling period, from 2020 to 2050. The alternative scenario presented an efficiency improvements, due advancement of solar-Promotion, clean-biomass, it’s a hypothesis which is based on the reference scenario, to assess the effects of public policy support for RE enrolment with associated cost. It should be noted that any energy-technology share, is ultimately determined by results of cost competition of different technologies. The alternative scenario, was modeled and simulated while adjusting the variables i.e . share-weight value and over-night capital cost of PV, this trial mechanism while choosing-varying close-range of figured values under PV analysis was monitored and balanced through (GCAM- EML) simulation until 20% government commitment target was arrived at. Under solar PV Sub- sector model analysis, the share-weight of PV technology under “results analysis” model-simulation, was varied, right from range of 1.00 to 0.17, of its over-night capital cost. This 0.17 was simulated and applied from 2025-2050 excluding 2015 – 2020 (base year) with a no further adjustment. The intent of this, implied that the government is assumed to support about 50% to solar promo increment, to subsidies the LCOE, aiming to arrive at policy target of 20% generation by share to the electricity mix. The above projection was considered based the underlying assumptions data from Uganda energy system pendant on – Hydro between and / or above 80% shared generation, in account that it might not go below 75% at BAU with fixed value of 75% share from 2025 – 2050, this was the fixed hydro scenario case. Whereas SWOT analysis was meant to comprehensively evaluate the structural relationship between strategies meant to ensure energy transition by 2050. Results: Uganda’s energy system scenario, predicts that due to her RE resource in 2020, after introduction of solar PV, its share stood at 0.13% and projects a 20.79% share by 2040, under reference case. However, in the alternative case, the solar- Promotion alone without looking at the merged scenarios, there exists an exponential growth in the share of solar energy. In 2020, 0.13% of electricity came from solar. And the results shows that in 2040, the share of solar will growth up to 44.11. % almost surpassing the national policy of 20% target for solar generation share. In 2040, the total electricity generation, simulated solely from solar shoots up to 69,532 (GWh). By Looking at the 2050’s energy transition pathway, this study estimated a total investment cost of USD $ 940,831,900 under an alternative scenario with a significant PV incremental generation share of 9408.319 (GWh) from 6993.552 (GWh) at USD $ 699,355,200 from 2025. The CO2 emissions reduction projections for the electricity sub-sector were analyzed, and the results that under the merged scenario, there is a significant drop in CO2 emissions for from 2020 and 2040, it’s a promising scenario for waning down CO2 emissions, however in the fixed hydro scenario, results showed a slight increase from 2020 up to 2040 of 0.2055 MtCO2e and 1.9695 MtCO2e, respectively. Conclusion: The solar PV scenario if adopted, will stimulate energy transition drive by 2050 at a cost of approximately USD $ 978,163,202, which presupposes a significant 0.27% of the country’s GDP. The energy transition strategic action and plan (ETSAP) based on a weighed-score from various key influencing factors is drawn applicable to Uganda’s case scenario. An ideal sequential structure of stages to a strategic model [bottom-top model] for energy transition pathway is formulated as a country’s benchmark. In quest to address adverse effects from environment (deforestation) and energy poverty. In this study, the alternative scenario (under the model) is recommended to be adopted by government in consideration of foreign climate funding pledges and support from the development partners for sustainably achieve the energy transition target by 2050. Key words: Renewable energy, Energy transition, GCAM-EML, SWOT analysis, Uganda.
학위논문(석사)--융합에너지학과,2024. 2
Keywords: Energy transition; GCAM-EML; Renewable energy; SWOT analysis; Uganda